The Influence of Emotional Intelligence, Academic Stress, and Teaching Methods on Student Learning Satisfaction - Masfufah; Didit Darmawan (Journal of Practice Learning and Educational Development, 2024)
This study aims to analyze the influence of emotional intelligence, academic stress, and teaching methods on student learning satisfaction. Emotional intelligence is seen as capable of helping students manage their emotions and adapt to academic demands, while academic stress, to a certain extent, can serve as a motivator for achieving learning outcomes. In addition, the appropriate teaching methods are believed to play a dominant role in enhancing student learning satisfaction. The research method used is quantitative with a multiple linear regression approach. The research population consists of students from Sunan Giri University Surabaya, with purposive sampling technique involving 100 respondents from various study programs and semester levels. The analysis tool used is multiple linear regression. The research results show that simultaneously, emotional intelligence, academic stress, and teaching methods significantly affect student learning satisfaction. Partially, all three independent variables have a positive and significant impact, with teaching methods being the dominant factor. This indicates that emotional management, the ability to cope with academic pressure, and appropriate teaching strategies are crucial in determining student learning satisfaction. Thus, this research provides practical implications for higher education institutions to enhance student learning satisfaction thru the development of students' soft skills and innovations in teaching methods.